PARAMETERS OF NATIVE SILVER FORMATION IN THE AG-FE-S SYSTEM BASED ON THE EMF DETERMINATION AT 518-728 K AND 1-5000 BAR TOTAL PRESSURE - Chareev D.A.; Bortnikov N.S.; Osadchii E.G.; Shapovalov Yu.B.; Zhdanov N.N. (My University, 2006)
The phase relations in the Ag–Fe–S system have been studied with the method of solid-phase annealing at the pressure of natural vapor. The metallic silver–pyrite assemblage is stable below 521 ± 8 K. At a higher temperature, this assemblage gives way to the argentite–pyrrhotite–pyrite assemblage, but phase relations remain principally unchanged up to 805 K. Less than 0.1 at % of Ag can dissolve from sulfides and argentite. The Fe1 – xS compositions in the Ag 2S + 'FeS' + FeS 2 assemblage at >521 ± 8 K are identical to those in the binary 'FeS' + FeS 2 assemblage.
Keywords: Ag–Fe–S system